(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2025)
Palmyarh is a significant tree, has an ethno-scientific and umbilical connection with Tamil culture. Thus, its products have an intimate social linkage with culture, including birth to death related rituals. Due to this, it is designated as a State Tree of Tamil Nadu. Karthigai festival commemorates the birth of the Tamil god Karthikeyan. A hand-rotating, homemade firecracker known as Karthigai Maavoli is an inevitable component of the Karthigai festival celebration. Tamil people have been celebrating the Karthigai festival for centuries, dating back to the Sangam period. The palmyarh male tree spadix charcoal powder is a main ingredient for making Maavoli, it is a non-explosive homemade firework/cracker, which is a highly safe and ecofriendly product. The invention of chemical fire crackers is a reason for the homemade fire crackers to lose their sparkle. The younger generation is increasingly unfamiliar with traditional firework-making, its performance methods, and cultural ties to the Karthigai festival. Due to the younger generation’s inexperience, interest and lack of documented information about Maavoli, people are burning bicycle tires rather than maavoli bags, which are hazardous to the environment. Hence, an effort and study made with objective to document materials for Maavoli preparation, validation and compilation of relevant information on status of Maavoli celebration by literature survey and interviews with rural people in the selected district of Tamil Nadu. The manuscript also indicates on possible ingredient to make an ideal Maavoli bag. This new ingredient in Maavoli bag is first time reported here for exposure and wide communication.